2020
DOI: 10.1177/2158244019900186
|View full text |Cite
|
Sign up to set email alerts
|

Does Facebook Commerce Enhance SMEs Performance? A Structural Equation Analysis of Omani SMEs

Abstract: This research aims to identify the factors affecting the adoption of Facebook commerce, in specific the adopted Facebook advertisements for both small and medium enterprises (SMEs) and how this contributes to enhancing such SMEs’ organizational performances. Specifically, ease of use, demographic targeting, interaction, and brand awareness are regarded as the key factors that can influence Facebook’s advertisements adoption. However, three organizational performance dimensions (efficiency, flexibility, and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 31 publications
(43 reference statements)
1
62
0
Order By: Relevance
“…[26] has established in her analysis on the business trends in the UK that for many years, operation cost is a major impediment among entrepreneurs and local investors for the reason that external factors such as input costs are demanding while the market becomes moody at times. According to [28], while Muscat is the center for business and information, the government and other stakeholders need to recognize that there are numerous challenges and there is a need to streamline business in the city to make SMEs competitive in the local and international markets with the increased adoption of e-commerce.…”
Section: Discussion Of Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] has established in her analysis on the business trends in the UK that for many years, operation cost is a major impediment among entrepreneurs and local investors for the reason that external factors such as input costs are demanding while the market becomes moody at times. According to [28], while Muscat is the center for business and information, the government and other stakeholders need to recognize that there are numerous challenges and there is a need to streamline business in the city to make SMEs competitive in the local and international markets with the increased adoption of e-commerce.…”
Section: Discussion Of Research Findingsmentioning
confidence: 99%
“…This study revolved around the processes of SMEs and other small-scale business industries, in which the risk management strategies and approaches are occasionally done and are established without formal documents and strategies. Interviews allude to a purposeful discussion between the researcher and respondents with the intent of collecting data that is relevant to the investigation [28]. The interviews were conducted face-to-face with the respondents.…”
Section: Research Strategymentioning
confidence: 99%
“…Research measurement model using Confirmatory FactorAnalysis. (Ruzzier et al, 2007) (Alraja et al, 2020). To the collect primary data, sampling design to provides a methodologys for the appropriate respondent sample size.…”
Section: Research Methodology Study Contexts and Proceduresmentioning
confidence: 99%
“…According to Alraja, Khan, Khashab and Aldaas (2020), social media has been widely used to attract and encourage many unemployed individuals to create SMEs through government support. Specifically, Facebook has been used because it is relatively more social, interactive, and consumer-concentrated than other social media platforms (Dahnil, Marzuki, Langgat&Fabeil, 2014).…”
Section: Facebook Adsmentioning
confidence: 99%
“…In addition, the use of Facebook ads for advertisement strengthens the relationship between SMEs and consumers; Consequently, the improved relationship between SMEs and consumers increases sales volume, which, therefore, improves the organization's overall performance. Generally, Alraja et al (2020) suggested that the use of Facebook ads positively impacts the sustainability of SMEs by enhancing the individual's life quality, rendering an organization's profitability, and enhancing the relationship between the SMEs and the government.…”
Section: Facebook Adsmentioning
confidence: 99%